1986
DOI: 10.1152/ajpgi.1986.250.4.g553
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide receptor antagonist [4Cl-D-Phe6, Leu17] VIP

Abstract: From structure-activity relationship studies of rat growth hormone-releasing factor (rGFR) on the vasoactive intestinal peptide (VIP) receptor in an in vitro preparation of exocrine pancreas, we predicted that [4Cl-D-Phe6, Leu17]VIP would be a competitive antagonist for the action of VIP. Micromolar concentrations of synthetic [4Cl-D-Phe6, Leu17]VIP competitively antagonized VIP-stimulated amylase release in the pancreatic preparation and VIP-stimulated short-circuit current changes in a colonic tumor cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…A roughly identical Ki value of 1 pM was found for the antagonist, when considering VIP, PHI and [ D -P~~~I P H I as agonist (Fig. 7): this Ki value compares favorably with the Ki value of 1.5 pM observed for another VIP antagonist, [~-( C l~) P h e~, Leu"]VIP, on dispersed guinea pig pancreatic acini [21]. c) Secretin(7 -27), a secretin antagonist without agonist efficacy (Fig.…”
Section: Dose-effect Curves Of ( a ) Rat Pancreatic Adenylate Cyclasupporting
confidence: 72%
“…A roughly identical Ki value of 1 pM was found for the antagonist, when considering VIP, PHI and [ D -P~~~I P H I as agonist (Fig. 7): this Ki value compares favorably with the Ki value of 1.5 pM observed for another VIP antagonist, [~-( C l~) P h e~, Leu"]VIP, on dispersed guinea pig pancreatic acini [21]. c) Secretin(7 -27), a secretin antagonist without agonist efficacy (Fig.…”
Section: Dose-effect Curves Of ( a ) Rat Pancreatic Adenylate Cyclasupporting
confidence: 72%
“…PACAP(2-27) was already 50-fold less potent than PACAP(1-27) for binding but retained 90% of its intrinsic effect on adenylate cyclase. In line with other members of this family of peptides (including VIP, secretin and glucagon) [17,18,[23][24][25][26][27][28][29][30][31][32][33], it appears that, upon receptor recognition, the first two residues of PACAP(1-27) played an important role in adenylate cyclase activation, but the N-terminal His1 was not absolutely required. After further deletion, the of PACAP(3 -27), PACAP(5 -27), PACAP(6 -27), PACAP(7 -27) and PACAP(9 -27) were, respectively, 1 500-, 500-, 200-, 1500-and 3800-fold higher than that of PACAP(1-27), and these five PACAP fragments, having lost the ability to stimulate adenylate cyclase, behaved as antagonists (Table 2), i.e.…”
Section: Fig4 Correlation Between Ics0 (A) and K (Or Ki) (B) Of mentioning
confidence: 52%
“…The inhibitory action of endogenously released VIP on ACh release from the vagus nerve terminal would explain the less prominent summation of ej.ps and contractions in the cat trachea than in the dog trachea. In the dog trachea, the prominent summation of ej.ps and contraction in the presence of indomethacin, the lack of effect of VIP antagonists or of VIP antiserum (Hakoda & Ito, 1990) on excitatory neuroeffector transmission even though the cholinergic nerve fibres are also immunoreactive to VIP (Dey et al, 1981) al., 1985;Pandol et al, 1986), showed no effect on the NANC-induced relaxation in the guinea-pig and cat trachea (Ellis & Farmer, 1989;Hakoda & Ito, 1990). Furthermore, Ellis & Farmer (1989) reported that these agents were without effect on the responsiveness of the guinea-pig trachea to exogenous VIP or PHI.…”
Section: Methodsmentioning
confidence: 99%